Analysis of experimental practices for basic cycle through comic (Research, Society and Development, 2022)
This work stems from scientific literacy from the creation of a comic strip referring to experimental practices. The activities took place from March to April 2021 during the COVID-19 pandemic in the 1st year class of the 1st cycle of EB1 at Castelo of Figueira da Foz, Portugal. The present work aims to analyze the scientific literacy acquired from experimental practices on colors through the construction of comic books addressing these experiences as a theme. Initially, the students participated in an experimental class a remote system through an online class during the class period. Three experiments were approached under the theme of colors. Subsequently, an online questionnaire was passed to ascertain the students' interest in the experimental class. Subsequently, a workshop on producing comics was held in the classroom asynchronously. After the workshop, the students had a period of three weeks during the art classes and study of the environment to make the stories. After the stories were completed, they were handed over for analysis. It was observed, through the graphic language, a methodological sequence of the elaboration of the practices present in the plots of the stories, which shows a satisfactory result.